Essential Oil Composition and Biological Activities of Eucalyptus globulus Leaves Extracts from Tunisia. Issue 2 (4th March 2017) - Jerbi, Amel; Derbali, Amal; Elfeki, Abdelfatteh; Kammoun, Majed
Abstract: This study was designed to examine chemical composition and antioxidant activity as well as the in vitro α-amylase pancreatic lipase and angiotensin-converting enzyme inhibitory activities of the essential oil and various extracts of Eucalyptus globules leaves collected from Sfax (Tunisia). The main constituents (≥ 7%) identified by GC-MS in the essential oil of E. globulus are 1, 8-cineole (48.2%), α-pinene (16.1%), γ-terpinene (8.9%) and p -cymene (8.8%). The IC50 values of essential oil, hexane, ethyl acetate and methanolic extracts against α-amylase were 27.29, 27.10, 31.7 and 48.01 μg/ml respectively. However, the IC50 values of essential oil, ethyl acetate and methanolic extracts against pancreatic lipase were 17.85, 20.16 and 29.76 μg/ml respectively, suggesting powerful anti-diabetic and anti-obesity effects. Antioxidant activity (IC50 =23 μg/ml) and hypotensive activity (IC50 =98 μg/ml) of the methanolic extract were found to be the highest compared to the other extract. Based on these results, E. globulus could be used as a significant source for natural products with interesting medicinal properties.